EYE TRACKING AND AUTONOMIC NERVOUS SYSTEM REACTIVITY DURING PERCEPTION OF VISUAL ENVIRONMENTS OF DIFFERENT COMFORT - Natalya Zvyagina; Lyudmila Sokolova; Lyudmila Morozova; Svetlana Lukina; Anna Cherkasova (European Scientific Journal, ESJ, 2014)
Participants included 50 individuals of age20.5. Oculo-motor reactions and sympathetic skin response (SSR) have been monitored during perception of visual stimuli of different comfort. The research is unique in that sympathetic skin response registration is realized at the same time with eye tracking, giving thus an opportunity of analyzing cognitive visual-motor activity while viewing images and related physiological parameters, which reflect the autonomic nervous system (ANS) functional status. Activation of the ergotropic brain system has been found during uncomfortable stimuli perception that is to provide vegetative mobilizationof organizm. When comfort visual stimuli were presented to participants the trophotropic brain system was activated, indicating relaxing influence of the stimuli. An eye tracking analysis revealed an increase of dynamic and static parameters during uncomfortable images perception. This increase characterizes high tension of visual functional system. A correlational analysis has revealed diverse and significant relations between eye tracking and SSR measures in comfort stimuli perception. This relies upon consensual functioning of the ANS and oculo-motor system, providing optimal mode of visual analyzer.